’n Gesprek oor die teologie van Heyns - Theron, D. F. (Verbum et ecclesia, 1994)
A discussion about the theology of Heyns Heyns developed a theology with the kingdom of God as central theme. He was strongly influenced by the philosophy of Stoker of South Africa. This resulted in a more philosophical theology rather than a biblical theology. After his Theology of obedience had been developed, a more theological emphasis came to the fore, but it was still very much dominated by his philosophical approach. An outstanding and original characteristic feature of the way he interprets the kingdom of God, is that it has its starting point at creation and gradually develops through history and comes to fullness at the end of history. At this point in time the boundaries of this world and the kingdom of God will overlap completely.